Morphological capability of the uterine scar after the previous caesarean section - Н. Р. Ковида; Н. П. Гончарук; О. О. Дядик (Publishing House TRILIST, 2020)
Purpose of the study was analysis the particulars of morphological capability of the uterine scar after the previous Caesarean section. Materials and methods. The paper presents the data of morphological study of 100 fragments of uterine scar tissue, which were divided into two groups on clinical grounds. The first group included 50 fragments of the so-called "clinically capable" scars, and the second group included 50 fragments so-called "clinically incapable" scars. Assessment of the uterine scar tissue was performed by immunohistochemical study with monoclonal antibodies, as well as Van Gieson's and Masson's stain. Study results. More pronounced structural changes of the actual muscle fibers and microcirculatory disorders were observed in form of changes in architecture and areas of myometrium tissue homogenization in the group with "clinically incapable" scars using hematoxylin and eosin stain of the uterine scar tissue. In the differentiation of fibrous connective tissue using Van Gieson's stain method in the group of "clinically incapable" scars were manifested as replacement of muscular tissue with connective tissue with the formation of discrete muscular tissue fibers, and expressed perivascular fibrosis. Degenerative-ischemic changes of uterine scar tissue were found in the group of "clinically incapable" scars using immunohistochemical study with monoclonal antibodies to α-SMA. Pathomorphological study of the uterus scar revealed that hypoxic-degenerative changes and irregularity of maturation of collagen tissue, as well as pronounced replacement of muscle tissue with connective tissue with formation of separately immersed fibers of muscle tissue took place in the "clinically incapable" group. Immunohistochemical study with monoclonal antibodies to α-SMA and to CD31 revealed the more pronounced degenerative ischemic changes in the "clinically incapable" group. Conclusions. The revealed changes in the structure of the uterine scar tissue indicate that the state of myometrium, vascular component, regenerative capacity in the "clinically incapable" group on 43.4% worse than in the "clinically capable" group, and may manifest negatively with excessive functional loading of the uterine wall during pregnancy and childbirth.